Bolstering the moderating effect of supervisory innovative support on organisational learning and employees' engagement - Olunike Joel Opeyemi; Chinoyen Love Moses; Ebeguki Edith Igbinoba; Maxwell Ayodele Olokundun; Odunayo P. Salau; Oluwatunmise Ojebola; Olufunke P. Adebayo (Administrative Sciences, 2023)
Organisational learning, as the process of continuous information acquisition, dissemination and exploitation, often leads to an organisation's competitiveness. Hence, this study examined the relationship between organisational learning and employee engagement. The study also investigated the extent to which supervisory innovative support moderates organisational learning and the effectiveness of employee engagement. Five hundred forty-one (541) participants were surveyed using stratified and purposive sampling methods to make up the sample size. To be more precise, Smart Partial Least Square (PLS 3.0) was used to analyse the relationship between the study's variables. The hypothesis test found that supervisory innovative support moderated the relationship between organisational learning and employee engagement to a significant extent (R2 = 0.810 Adjusted R2 = 0.806 p-value 0.05). As a result, the study recommends that pharmaceutical companies clarify their policies and culture to employees so that supervisory support can lead to higher employee engagement through organisational learning. Pharmaceutical firms should also provide financial incentives based on employee duration or distinctive contributions to company goals.
Keywords: 350; employee engagement; innovation; job commitment; supervisory innovative support